"Dick Tracy meets Gruesome" - Rawlins, John, 1902-1997; Karloff, Boris, 1887-1969; Byrd, Ralph, 1909-1952; Gwynne, Anne, 1918-2003; Gould, Chester; RKO Radio Pictures; Cinetel Films ([Los Angeles, CA] : RKO Radio Pictures, Inc., 1947)
A gang of criminals, which includes a piano player and an imposing former convict known as 'Gruesome', has found out about a scientist's secret formula for a gas that temporarily paralyzes anyone who breathes it. When Gruesome accidentally inhales some of the gas and passes out, the police think he is dead and take him to the morgue, where he later revives and escapes. This puzzling incident attracts the interest of Dick Tracy, and when the criminals later use the gas to rob a bank, Tracy realizes that he must devote his entire attention to stopping them. --
Originally released as a motion picture in 1947.
Movie distributed by Cinetel for Digitalia Film Library.
Based on the comic strip by Chester Gould.
Boris Karloff, Ralph Byrd, Anne Gwynne, Edward Ashley.
Director of photography, Frank Redman; editor, Elmo Williams; music, Paul Sawtell.
In English or Spanish.
Keywords: Tracy, Dick (Fictitious character) -- Drama; Bank robberies -- Drama; Police films; Fiction films; Feature films; Internet videos; Streaming video